The Perception of UTHM Pagoh Students on the Implementation of Mydigital ID in Malaysia - Aziz Jaafar, Aziz Ridzwan Ruzaini; Mohd Asrah, Norhaidah (Enhanced Knowledge in Sciences and Technology, 2025)
MyDigital ID is a Malaysia national identity management and transaction signing platform designed to address the vulnerabilities of its contemporary implementation such as insecure communication channels and storage of user credentials. MyDigital ID helps to enable fast and secure execution of identity authentication for users’ interaction with entities both in person and online. However, the successful implementation of MyDigital ID faces challenges due to negative public perceptions despite its potential benefits, particularly concerning privacy, data security, and accessibility. This study investigates the perceptions of Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh students toward the implementation of MyDigital ID. The objectives of this study include determining the relationship between MyDigital ID awareness levels and demographic characteristics using Chi-Square analysis, identifying the association between MyDigital ID and MyKad functionality via correspondence analysis, and distinguish the factor and potential barriers to the adoption of MyDigital ID using factor analysis. The results from Chi-Square analysis reveal significant relationships between MyDigital ID awareness levels and demographic characteristics. Correspondence analysis shows that respondents perceive MyKad as more functional and reliable compared to MyDigital ID, particularly for authentication purposes. Additionally, factor analysis identified four key barriers to adoption. These are data privacy and security, usability and interface experience, system efficiency and performance, and user support and ease of access. The findings underscore students’ concerns about data privacy, system usability, and accessibility, despite the platform’s compliance with regulatory acts and its potential to improve educational access and administrative efficiency. This study insights are crucial for addressing barriers to adoption, building trust, and enhancing the integration of MyDigital ID within Malaysia’s digital landscape.